2020
DOI: 10.1007/s00418-020-01859-9
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of protein (human galectin-3) design on aspects of lectin activity

Abstract: The concept of biomedical significance of the functional pairing between tissue lectins and their glycoconjugate counterreceptors has reached the mainstream of research on the flow of biological information. A major challenge now is to identify the principles of structure–activity relationships that underlie specificity of recognition and the ensuing post-binding processes. Toward this end, we focus on a distinct feature on the side of the lectin, i.e. its architecture to present the carbohydrate recognition d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 98 publications
1
21
0
Order By: Relevance
“…In light of recent findings, other functional oligomeric states of LGALS3 than pentamers, may exist via the dynamic self-association of its intrinsically disordered N-terminal domain [ 156 ]. In a very recent study, Farhadi and colleagues, using engineered LGALS3 constructs (from dimers to hexamers) based on α-helical coiled-coil scaffolds, confirmed that glycan-binding properties, clustering and extracellular signaling activities of LGALS3 depend on architecture and valency, extending previous work with engineered LGALS3 [ 157 – 159 ]. The authors of this study also highlighted that the relatively large integral membrane glycoprotein protein tyrosine phosphatase receptor type C (PTPRC/CD45) (in contrast to smaller glycoproteins such as CD7) regulates membrane glycan clustering and cell death signaling activities of synthetic LGALS3 oligomers [ 157 ].…”
Section: Glycans and Endocytosissupporting
confidence: 58%
“…In light of recent findings, other functional oligomeric states of LGALS3 than pentamers, may exist via the dynamic self-association of its intrinsically disordered N-terminal domain [ 156 ]. In a very recent study, Farhadi and colleagues, using engineered LGALS3 constructs (from dimers to hexamers) based on α-helical coiled-coil scaffolds, confirmed that glycan-binding properties, clustering and extracellular signaling activities of LGALS3 depend on architecture and valency, extending previous work with engineered LGALS3 [ 157 – 159 ]. The authors of this study also highlighted that the relatively large integral membrane glycoprotein protein tyrosine phosphatase receptor type C (PTPRC/CD45) (in contrast to smaller glycoproteins such as CD7) regulates membrane glycan clustering and cell death signaling activities of synthetic LGALS3 oligomers [ 157 ].…”
Section: Glycans and Endocytosissupporting
confidence: 58%
“…di- or tetramer) affects staining profiles (and functions). Respective studies have recently been initiated for galectins [ 30 , 60 ].…”
Section: Endogenous Lectins In Cyto- and Histochemistrymentioning
confidence: 99%
“…The pairwise interaction between lectins and their glycoconjugate reaction partners in animal tissues is of importance in many patho-physiological processes (Cummings 2019;Duan and Paulson 2020;Kaltner et al 2019). In their present study, García Caballero et al (2020) aimed to identify principles of structure-activity relationships that underlie specificity of recognition and the ensuing post-binding processes. To this end, they focused on the architecture of the carbohydrate recognition domain (CRD) of the multifunctional human galectin-3 (Gal-3) and engineered variants with different modular assembly to relate protein design to activity.…”
Section: Protein Design and (Gal)lectin Activitymentioning
confidence: 99%